Competitive firm and resource allocation under uncertain capital service. - Martin, Robert E.; Yu, Eden S. H. (Southern Economic Journal, 1990)
A study examined the effects of uncertain capital service and industry risk pooling on the behavior of a competitive firm and the allocation of resources. A two-sector general equilibrium framework was used. It was found that capital service uncertainty leads to a reduction in a firm's output, inputs, and capital labor and that a reduction in capital reliability or a marginal increase in uncertainty produces a similar effect. Other findings involved the effect of changes in factor endowments and output prices on sectoral factor intensities, input utilization, factor rewards, and output levels. In addition, it was shown that, given risk aversion, the factor-price equalization theorem fails to hold and the Stopler-Samuelson and Rybczynski theorems are only partially valid. The results in the traditional general equilibrium models were mitigated or even reversed by the presence of uncertain capital services.